Wild growing flora of Pusztaszabolcs and its surroundings, a typical agricultural region of Central-Hungary - Tamás, Júlia; Csontos, Péter (JOURNAL OF LANDSCAPE ECOLOGY, 2013)
This paper reports the flora of the surroundings of the town Pusztaszabolcs, Hungary, based on two grid cells (nos 8878/1 and 8878/3) surveyed during the Hungarian Flora Mapping Project in the years 2003 and 2004. Total surveyed area was 68.75 km2, covered by loess derived soils with mildly undulating surface between 110 m and 184 m above see level. Typical land use of the region was extensive agricultural fields (mainly with maize, sunflower and wheat). Species numbers were: 260 and 321 in grid cells 8878/1 and 8878/3, respectively, whereas total number of species in the studied area was 366. Sorensen’s index showed a similarity of 74% between the floras of the two grid cells, therefore, evaluation of their vegetation was based on the joint species list. In the gradient of natural vs. degraded status of vegetation the studied region was considered rather degraded since about 60% and 63% (depending on the evaluation method applied) of the species pool was formed by species indicating degradation and disturbances. In a subsequent analysis, when the sub-set of species present in both flora mapping grid cells were considered (s=215), the ratio of species indicating degradation increased to 63% or 74% depending on the evaluation method applied. The natural loess flora (that was typical to the region prior to extensive agricultural use) was restricted to narrow linear landscape elements (e.g. field margins, green corridors of railway lines, etc), and was impoverished due to repeated anthropogenic disturbances. The surviving species pool was formed by less sensitive members of the loess vegetation: Agropyron intermedium, A. pectinatum, Astragalus cicer, Euphorbia pannonica, Festuca rupicola, Lithospermum officinale, Marrubium peregrinum, Melica ciliata, Melica transsilvanica, Nepeta cataria, Nonea pulla, Peucedanum alsaticum, Rapistrum perenne, Salvia pratensis, S. nemorosa, S. verticillata, Stipa capillata and Thalictrum minus. Taraxacum serotinum was the only member of the protected-by-low elements of the loess vegetation.